High dose salvage therapy with dose intensive cyclophosphamide, etoposide and cisplatin may increase transplant rates for relapsed/refractory aggressive non-Hodgkin lymphoma. Issue 12 (December 2013) - Vijay, Archana; Duan, Qiuli; Henning, Jan-Willem; Duggan, Peter; Daly, Andrew; Shafey, Mona; Bahlis, Nizar J.; Stewart, Douglas Allan
Abstract Only one-quarter to one-third of patients with relapsed/refractory aggressive non-Hodgkin lymphoma (r/r-aNHL) treated with common salvage chemotherapy regimens and autologous stem cell transplant (ASCT) achieve 5-year progression-free survival (PFS). Worse outcomes have been reported after failure of prior rituximab-containing induction, initial time to progression (TTP) < 1 year or age-adjusted International Prognostic Index (aaIPI) = 2–3 at relapse. In Calgary, we have treated patients with r/r-aNHL with dose-intensive cyclophosphamide 5.25 g/m2, etoposide 1.05 g/m2 and cisplatin 105 mg/m2 (DICEP) for both re-induction therapy and autologous blood stem cell mobilization. In this study we retrospectively analyzed 113 consecutive transplant-eligible patients with r/r-aNHL who received one cycle of DICEP (n = 93) or R-DICEP (n = 20) from 1995 to 2009. Patient characteristics included: median age = 49 years (22–69); TTP < 1 year = 85; elevated lactate dehydrogenase (LDH) = 60; Eastern Cooperative Oncology Group performance status (ECOG) 2–4 = 42; aaIPI 2–3 = 59; bulk > 10 cm = 26, prior rituximab = 27. The median number of CD34 + cells collected was 19 × 106/kg (0.3–142), 83.5% responded and 90% (102) proceeded to ASCT. The 5-year PFS rate was 42% for all patients, 32% for those with relapse aaIPI = 2–3, 35% for initial TTP < 1 year and 56% for those who failed initial rituximab induction. In conclusion, (R)DICEP is an effective re-induction regimen for r/r-aNHL, leading to excellent stem cell mobilization, a high chance of proceeding to ASCT and encouraging long-term PFS rates.